PENGARUH KEBUDAYAAN KONTEMPORER DALAM PERANCANGAN ARSITEKTUR MAL (DIMENSI: Journal of Architecture and Built Environment, 2004)
Market is traditionally known as the place where the seller and the buyers meet. In its development, it grows to be big shopping centers and even malls. Along with it, the concept of market has also changed within this building. It is not only the place where the transaction between the sellers and the buyers happen but also it expands to be the one where each person has turned to be the "player" in the nowadays "cultural-theatre". Being the designers, the architect is challenged to respond the changing pattern in the society by making use of the building.Abstract in Bahasa Indonesia : Pasar dikenal sebagai tempat dimana penjual dan pembeli bertemu. Dalam perkembangan lebih lanjut muncul pusat-pusat pertokoan yang sangat besar sampai hadirnya shopping-mall. Di dalam bangunan inilah konsep pasar secara tradisional telah berkembang, tidak saja tempat transaksi antara penjual dan pembeli, tetapi telah melebar menjadi tempat dimana setiap individu telah menjadi "pemain" di dalam sebuah teater kebudayaan masa kini. Arsitek sebagai perancang bangunan harus menyikapi perubahan-perubahan perilaku yang terjadi di masyarakat dalam menggunakan bangunannya.Kata kunci: kebudayaan kontemporer, arsitek, arsitektur mal, kebudayaan milenium tiga.